Validação dos métodos de identificação do sexo em tilápias do nilo (Oreochromis niloticus, Linnaeus, 1757), revertidas com rações contendo diferentes granulometrias e de diferentes idades - Makino, Lilian Cristina [UNESP] (2005)
This work evaluated three methods of sexual identification of Nile tilapias with ages of 30, 60 and 90 days of age reverted through administration of androgen 17u¬methyltestosterone added to the rations of different diameters (0.25; 0.35 and 0.50 mm) in dosage of 60 mglkg of ration. To the biometricals parameters as weight and length total were used a completely randomized design in subdivided instalments with three treatments and three repetitions, where the instalments were the three diameters of ration and the subinstalments, the three ages. In the end of this work, fishes feeded with diameters 0.35 and 0.25 mm, respectively, have obtained the best results for weight (14.42 g and 13.36 g) and length total (83.13 mm and 82.72 mm), although being statisticaly not significant. In the presence of the three methods of sexual identification evaluated, histology of gonads has shown the most confident diagnosis